2018
DOI: 10.15537/smj.2018.10.23098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of dexmedetomidine and remifentanil on pain with the analgesia nociception index in the perioperative period in hysteroscopies under general anesthesia

Abstract: Objectives:To compare analgesia nociception index (ANI) values, visual analog scale (VAS) values, and hemodynamic parameters in hysteroscopy patients who received remifentanil and dexmedetomidine during general anesthesia.Methods:In total, 30 patients who underwent hysteroscopy between March and September 2016 at the University of Health Sciences Fatih Sultan Mehmet Health Research and Application Center, İstanbul, Turkey were included in this prospective study. Standard hemodynamic monitoring, ANI, and bispec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…The results showed that the rate of hemodynamic changes and pain intensity at 5, 10, and 30 minutes after the surgery were lower than those in the remifentanil group. They concluded that dexmedetomidine was effective in reducing patients' postoperative pain (P < 0.05) (22), which was in line with our findings. In South Korea (2016), a study compared the intravenous injections of dexmedetomidine, fentanyl, and remifentanil on postoperative hemodynamics, sedative quality, and postoperative pain control.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results showed that the rate of hemodynamic changes and pain intensity at 5, 10, and 30 minutes after the surgery were lower than those in the remifentanil group. They concluded that dexmedetomidine was effective in reducing patients' postoperative pain (P < 0.05) (22), which was in line with our findings. In South Korea (2016), a study compared the intravenous injections of dexmedetomidine, fentanyl, and remifentanil on postoperative hemodynamics, sedative quality, and postoperative pain control.…”
Section: Discussionsupporting
confidence: 90%
“…The results showed that the rate of hemodynamic changes and pain intensity at 5, 10, and 30 minutes after the surgery were lower than those in the remifentanil group. They concluded that dexmedetomidine was effective in reducing patients' postoperative pain (P < 0.05) ( 22 ), which was in line with our findings.…”
Section: Discussionsupporting
confidence: 89%
“…After a review of the titles and abstracts, 81 studies were selected and assessed for potential inclusion into this systematic review. After reading the full-text articles, 33 RCTs (published between 1994 and 2021) including 2209 participants were finally included ( Figure 1 ) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. No unpublished trials were identified with our eligibility criteria in the clinicaltrial.gov register.…”
Section: Resultsmentioning
confidence: 99%
“…It is metabolized by esterases independently of hepatic and renal functions, and was therefore eliminated at a more rapid speed than other anilidopiperidine opioids [ 27 ]. Remifentanil alone or in combination with adjunct agents has been widely utilized for general anesthesia in hysteroscopy [ 28 ]. In the present study, similarly, intravenous infusion of remifentanil 1.5 μg/kg in synergy with propofol 1.5 mg/kg and cisatracurium 0.1 mg/kg 1 min later were used for the induction of general anesthesia in all patients.…”
Section: Discussionmentioning
confidence: 99%